Expression patterns of class i histone deacetylases in osteosarcoma: A novel prognostic marker with potential therapeutic implications - Parunya Chaiyawat (2018)
© 2018 USCAP, Inc All rights reserved. Epigenetic aberrations are recognized as having pivotal roles in cancer etiology and progression. Histone deacetylases are among the most studied epigenetic modulators in various cancer types. The expression levels of class I histone deacetylase isoforms 1, 2, and 3 in patient-derived primary osteosarcoma cells (6 cases) was investigated, comparing them to normal bone graft-derived osteoblasts (6 cases) using the immunoblotting technique. Expression profiles of histone deacetylases in high-grade osteosarcoma tissue of 89 patients were examined and their association with clinicopathologic parameters and the patient survival was evaluated. Histone deacetylases were immunohistochemically stained on formalin-fixed paraffin-embedded biopsied tissue. Primary osteosarcoma cells expressed higher levels of histone deacetylase 1 and histone deacetylase 2, but lower levels of histone deacetylase 3 compared to benign osteoblasts. Overall, 82, 99, and 93% of 89 osteosarcomas showed nuclear expression of the histone deacetylase isoforms 1, 2, and 3, respectively. Low levels of histone deacetylase 1 were significantly associated with a high Enneking stage (P=0.014) and the presence of initial metastasis (P=0.040), while low levels of histone deacetylase 3 were significantly correlated with age >15 years (P=0.026). Univariate survival analysis found significantly shorter survival in the patients with a high Enneking stage (P<0.001), axial location (P=0.009), presence of initial metastasis (P<0.001), lowhistone deacetylase 1 expression (P=0.038), and low-all-histone deacetylases expression (P=0.016). Multivariate survival analysis showed that only axial location (P=0.011) and low-all-histone deacetylases expression (P=0.039) were independent prognostic factors. In subgroup analysis of stage IIB patients (n=45), only axial location and low-all-histone deacetylases expression were associated with shorter survival in both univariate and multivariate analysis (axial location, P=0.008 and 0.010; low-all-HDACs, P=0.013 and 0.038, respectively). Low levels of all-histone deacetylases expression were significantly associated with advanced disease status and short survival. These findings may be a guide to future use of histone deacetylase inhibitors in osteosarcoma patients.